The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1108/ijebr-08-2016-0241
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial intention of Danish students: a correspondence analysis

Abstract: Terms of use This work is brought to you by the University of Southern Denmark through the SDU Research Portal. Unless otherwise specified it has been shared according to the terms for self-archiving. If no other license is stated, these terms apply: • You may download this work for personal use only. • You may not further distribute the material or use it for any profit-making activity or commercial gain • You may freely distribute the URL identifying this open access version If you believe that this document… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 60 publications
1
49
0
4
Order By: Relevance
“…Fietze and Boyd [29] found that students prefer a career as employee showing a low EI. Henley et al [30] argued that Leadership skills, indicative of bridging cognitive social capital, are found to be strongly and significantly associated with entrepreneurial intentions through the mediating role of the core TPB constructs.…”
Section: Behavioral Approach: Theory Of Planned Behaviormentioning
confidence: 99%
“…Fietze and Boyd [29] found that students prefer a career as employee showing a low EI. Henley et al [30] argued that Leadership skills, indicative of bridging cognitive social capital, are found to be strongly and significantly associated with entrepreneurial intentions through the mediating role of the core TPB constructs.…”
Section: Behavioral Approach: Theory Of Planned Behaviormentioning
confidence: 99%
“…The degree of entrepreneurship of a region is linked to its economic prosperity and this is why policy makers are especially focused on fostering entrepreneurial activities, particularly among young people [4]. In this regard, entrepreneurial education has emerged as an important tool for that objective [5,6]. However, education currently offered in most countries does not promote, as it should, entrepreneurship or endow students with the much-needed "soft skills" such as leadership, responsibility, communication skills, or proactivity.…”
Section: Introductionmentioning
confidence: 99%
“…This variable was recoded to a dummy variable (0 = no entrepreneurial parents, 1 = entrepreneurial parents). The family background plays an important role in students' career choices and, subsequently, in their entrepreneurial intention (Fietze and Boyd 2017). Previous research has shown that a higher proportion of students from families with self-employed parents choose to become entrepreneurs (Laspita et al 2012).…”
Section: Methodsmentioning
confidence: 99%